2020
DOI: 10.1002/lno.11623
|View full text |Cite
|
Sign up to set email alerts
|

Thin layers in the coastal zone of Ubatuba, Brazil: Mechanisms of formation and dissipation

Abstract: Thin layers are vertically compressed, horizontally extensive, highly concentrated features comprised of plankton and/or particles. They are critical components of the marine ecosystem, likely playing a key role in the life histories and evolutionary trajectories of species found in, or, interacting with them. These structures have been reported in diverse marine environments around the globe. However, the mechanisms of thin layer formation/dissipation in the southwestern Atlantic Ocean were unknown until this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Thin phytoplankton layers are highly vertically compressed structures of photosynthetic micro-organisms (Durham & Stocker 2012) as found occasionally in coastal water bodies (Steinbuck et al 2009;Penninck et al 2020) and stratified lakes (Fee 1976;Jones 1988;Latasa et al 2017;Lofton et al 2020). Of significant importance to the ecology of aquatic systems, mechanisms underlying the formation, persistence and dissipation of thin phytoplankton layers are hot-spots in marine science (Durham & Stocker 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin phytoplankton layers are highly vertically compressed structures of photosynthetic micro-organisms (Durham & Stocker 2012) as found occasionally in coastal water bodies (Steinbuck et al 2009;Penninck et al 2020) and stratified lakes (Fee 1976;Jones 1988;Latasa et al 2017;Lofton et al 2020). Of significant importance to the ecology of aquatic systems, mechanisms underlying the formation, persistence and dissipation of thin phytoplankton layers are hot-spots in marine science (Durham & Stocker 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2009; Penninck et al. 2020) and stratified lakes (Fee 1976; Jones 1988; Latasa et al. 2017; Lofton et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the average winds for the observation period indicated a predominance of northeasterly winds, with greater intensities than those observed in winter. This wind pattern, acting parallel to the shoreline, favours coastal upwelling phenomena that lead to the subsurface intrusion of the cold, nutrient-rich waters of SACW onto the Ubatuba inner shelf (BRAGA; MÜLLER, 1998;PENNINCK et al, 2021), as observed during the study period (Fig. 3.4 D).…”
Section: Meteorological and Oceanographic Conditionsmentioning
confidence: 68%
“…SCMs are associated with thermoclines due to the accumulation of cells at neutral density depths along a vertical temperature gradient (DURHAM; STOCKER, 2012), and due to thermal stratification regulating the mixing of nutrients from deeper waters in the euphotic zone, being an important factor in determining nutricline (CULLEN, 2015;LEACH et al, 2018). Penninck et al, (2021), using an imaging system, found a great abundance of diatoms (microphytoplankton) in the SCM region, which developed in the form of a thin layer, on the inner shelf of Ubatuba. Our results indicate a great contribution of pico-and nanoplankton populations to the SCM, mainly Syne, PicoEuk, and NanoEuk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation